Mengukur Tingkat Pelayanan Pajak Bumi dan Bangunan Menggunakan Metode Service Quality (Studi Pada Dinas Pendapatan Daerah Kota Pekanbaru) - Karpen, Karpen; Rokib, Amul; Susandri, Susandri (Forum Kerjasama Pendidikan Tinggi, 2020)
The Regional Revenue Service (DISPENDA) of Pekanbaru City is a Regional Work Unit (SKPD) which is given the authority to collect and manage local taxes as well as the Regional Financial Management Officer (PPKD). As a tax collection SKPD that relies heavily on trust and public service, DISPENDA is demanded to provide optimal services by always prioritizing the quality of service so that taxpayers will feel satisfied and comfortable, especially for land and building tax (PBB). At present there are still complaints from taxpayers for services provided by DISPENDA, which results in laziness to pay taxes so that there are many tax arrears. For this reason, it is necessary to measure the level of service so that they can find out the complaints of taxpayers and DISPENDA employees can improve the quality of their services. This study uses the Servqual (Service Quality) method which includes variables or dimensions in the form of physical evidence (tangibles), reliability (reliability), responsiveness (responsiveness), assurance (assurance), and empathy (empathy). The results of the test show that each variable gets a positive customer indicator value, namely the physical evidence indicator = 3.82, guarantee = 3.61, empathy = 3.58, responsiveness = 3.66 and reliability = 3.67 from the standard value set. Variable physical evidence (tangibles), has a significant positive influence on satisfaction of taxpayers with an indicator value = 3.82, while the variables of empathy (reliability), reliability (responsiveness), and guarantee (assurance) effect but not significant impact on taxpayer services. This measurement of service level to provide public satisfaction in carrying out its obligations and increase land and building tax revenues for DISPENDA